Symmetry as a developmental principle in nature and art - Hahn, Werner (Singapore World Scientific, 1998)
Looking beyond the boundaries of various disciplines, the author demonstrates that symmetry is a fascinating phenomenon which provides endless stimulation and challenges. He explains that it is possible to readapt art to the sciences, and vice versa, by means of an evolutionary concept of symmetry. Many pictorial examples are included to enable the reader to fully understand the issues discussed. Based on the artistic evidence that the author has collected, he proposes that the new ars evolutoria can function as an example for the sciences.The book is divided into three distinct parts, each one focusing on a special issue. In Part I, the phenomenon of symmetry, including its discovery and meaning is reviewed. The author looks closely at how Vitruvius, Polyclitus, Democritus, Plato, Aristotle, Plotinus, Augustine, Alberti, Leonardo da Vinci and Durer viewed symmetry. This is followed by an explanation on how the concept of symmetry developed. The author further discusses symmetry as it appears in art and science, as well as in the modern age. Later, he expounds the view of symmetry as an evolutionary concept which can lead to a new unity of science. In Part II, he covers the points of contact between the form-developing process in nature and art. He deals with biological questions, in particular evolution.The collection of new and precise data on perception and knowledge with regard to the postulated reality of symmetry leads to further development of the evolutionary theory of symmetry in Part III. The author traces the enormous treasure of observations made in nature and culture back to a few underlying structural principles. He demonstrates symmetry as a far-reaching, leading, structuring, causal element of evolution, as the idea lying behind nature and culture. Numerous controllable reproducible double-mirror experiments on a new stereoscopic vision verify a symmetrization theory of perception.
Includes Index
Keywords: Nature (Aesthetics); Proportion -- Symmetry